Vai trò của niềm tin thương hiệu trên mạng xã hội và chứng nhận từ bên thứ ba trong mối quan hệ giữa tính minh bạch thương hiệu và sự gắn kết với thương hiệu - Đinh Văn, Hoàng; Phạm Thị Khánh, Huyền; Trần Thảo, An; Nguyễn Anh, Thư; Phạm Thùy, Linh; Nguyễn Linh, Chi (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2026)
This study examines the mediating role of social media brand trust and the moderating role of third-party certification in the relationship between perceived observability-based brand transparency and self-brand connection. Using partial least squares structural equation modeling (PLS-SEM) combined with the PROCESS Macro, 318 valid responses from Vietnamese consumers were analyzed. Results show that perceived observability-based brand transparency has positive direct and indirect effects (through social media brand trust) on self-brand connection. Third-party certification positively moderates the relationship between brand transparency and brand trust, and also positively moderates the mediating effect of brand trust. This research contributes to brand transparency theory and proposes managerial implications.
Keywords: Brand transparency; Social media brand trust; Third-party certification; Self-brand connection